2001
DOI: 10.2307/3871354
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Sequence Analysis Reveals Extensive Microcolinearity in the Lateral Suppressor Regions of the Tomato, Arabidopsis, and Capsella Genomes

Abstract: A 57-kb region of tomato chromosome 7 harboring five different genes was compared with the sequence of the Arabidopsis genome to search for microsynteny between the genomes of these two species. For all five genes, homologous sequences could be identified in a 30-kb region located on Arabidopsis chromosome 1. Only two inversion events distinguish the arrangement of the five genes in tomato from that in Arabidopsis. Inversions were not detected when the arrangement of the five Arabidopsis genes was compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
5
7
0
Order By: Relevance
“…We found that the region is colinear between A. thaliana and its relatives (Fig. 1), consistent with other studies demonstrating extensive synteny between cruciferous genomes (17)(18)(19)(20). In A. lyrata, A. petraea, A. cebennensis, and B. divaricarpa, the MAM cluster consists of three genes, which we designate MAMa, MAMb, and MAMc.…”
Section: Comparative Sequencing and Phylogenetic Analyses Reveal Complexsupporting
confidence: 90%
“…We found that the region is colinear between A. thaliana and its relatives (Fig. 1), consistent with other studies demonstrating extensive synteny between cruciferous genomes (17)(18)(19)(20). In A. lyrata, A. petraea, A. cebennensis, and B. divaricarpa, the MAM cluster consists of three genes, which we designate MAMa, MAMb, and MAMc.…”
Section: Comparative Sequencing and Phylogenetic Analyses Reveal Complexsupporting
confidence: 90%
“…We found a gene density of one gene every 9 kb, which is similar to previous findings in S. demissum (7.6 kb, [24]) and tomato (8 kb, [36,37]), but lower than A. thaliana (5 kb, [38]) and rice (6 kbp, [39]), and higher than in barley, where only three genes were found in a stretch of 60 kbp genomic DNA [40]. The overall GC content was 37% and 39.5% within the putative gene coding regions.…”
Section: Discussionsupporting
confidence: 91%
“…Similar patterns of interrupted co-linearity on the DNA sequence level were found among cereals [46] and between A. thaliana and rice [47]. In the highly collinear tomato genome [2,5], genomic sequences of 57 kbp and 106 kbp on chromosome 2 [48] and 7 [37], respectively, have been compared to the A. thaliana genomic sequence. These studies revealed syntenic blocks of comparable redundancy and size with respect to the A. thaliana syntenic regions.…”
Section: Discussionmentioning
confidence: 91%
“…The results showed that both the group A and group B regions displayed conserved synteny across the sequenced Brassicaceae genomes (Fig. 3), and were consistent with previous studies showing extensive synteny among Brassicaceae species (Rossberg et al, 2001;Boivin et al, 2004;Kuittinen et al, 2004;Franzke et al, 2011;Cheng et al, 2013).…”
Section: Two Ancestral Fmo Gs-ox Loci Contained Tandem Gene Arrays Ansupporting
confidence: 90%